PENGARUH PROMOSI JABATAN, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK TABUNGAN NEGARA (PERSERO) TBK. CABANG PADANG - Doni Marlius; Alfi Syahrin (LP2M Universitas Bina Bangsa, 2024)
Bank BTN faces unique challenges in maintaining productivity and service quality, especially in an era of increasingly competitive business environment and evolving market dynamics. In response to these challenges, the company needs to ensure that factors influencing employee performance are well understood and managed. This study aims to analyze the influence of job promotion, work discipline, and work motivation on employee performance at PT. Bank Tabungan Negara (Persero) Tbk. Padang Branch. Data collection was conducted through a survey using questionnaire, with measurement scale using Likert scale. The research sample consisted of 120 respondents from Bank BTN Padang Branch employees, with sampling method using total sampling or saturated sample. Data analysis techniques were performed using Descriptive Statistics, Multiple Linear Regression, and t-test to test hypotheses. The results of data analysis show that: 1) Job promotion has a positive and significant influence on employee performance at PT. Bank Tabungan Negara (Persero) Tbk. Padang Branch (β1 = 0.209, Sig. = 0.008 < 0.05). 2) Work discipline has a positive and significant influence on employee performance (β2 = 0.259, Sig. = 0.011 < 0.05) at PT. Bank Tabungan Negara (Persero) Tbk. Padang Branch. 3) Work motivation has a positive and significant influence on employee performance (β3 = 0.588, Sig. = 0.002 < 0.05) at PT. Bank Tabungan Negara (Persero) Tbk. Padang Branch